Note-Taking: skill and habit of consecutive interpreters - Elizabeth Hierrezuelo García; Hortencia Cruz López; Rafael Rodríguez Devesa (Cadernos de Tradução, 2023)
The notes taken by interpreters who work in the consecutive mode have a fundamental role in the interpreting process. These notes allow the interpreter not to be cognitively overloaded with remembering long segments of information or decontextualized data such as figures, names or series of elements that prove hard to retain in memory. Within the syllabuses of language majors in Cuba where translators and interpreters are trained, note-taking is conceived as a tool or a skill that needs to be automatic in order to be effective, both during formation and professional life of consecutive interpreters. Automaticity is directly related to habits and skills, whose close relationship makes it difficult to establish clear boundaries between one and the other in most situations, but skills and habits require different methodological approaches to be fostered. The aim of the present research is to determine whether note-taking is a professional skill or habit of interpreters. To fulfill such goal, the authors departed from the use of scientific observation during training sessions to continue with the critical appraisal of the documents reviewed as methods to reach conclusions and corroborate the results of the research.